Meningkatkan Pemahaman Siswa tentang Teks Iklan melalui Metode Presentasi Berbantuan Media Power Point di Kelas VIII C SMP Negeri 2 Kumai Tahun Pelajaran 2019/2020: Improving Student's Understanding of Advertising Text through Power Point Media Assistant Presentation Method in Class VIII C SMP Negeri 2 Kumai Year Lesson 2019/2020 - Stevanus, Stevanus (Anterior Jurnal, 2022)
In cycle I students still look confused with their assignments in class, this can be due to learning with computer media being a new thing and has not been applied before so the achievement of learning outcomes achieved by students is not optimal. With diligent effort and guidance, it is expected to increase students' understanding in the hope of increasing the achievement of better student learning outcomes. One of the factors that determine the success or failure of a person in learning is a factor that comes from within the person who is learning (internal). In the implementation of the second cycle of learning, the learning carried out by the teacher using the media-assisted presentation method, the power point-assisted presentation method, was better than the previous cycle and the explanation of the concept of the learning material could be understood by most students. The increase was due to the teacher's voice being able to be heard to the back, this could be influenced by the condition of the class that the teacher had mastered when the teacher delivered an explanation of the material. From the results of students' responses, students stated that they could understand what the media displayed. The results of the study: There was an increase in the percentage of the number of students who understood from the observations of 71.87% in the first cycle, 81.2% in the second cycle. The increased understanding of students affects the activeness of students to participate in the teaching and learning process.